2018
DOI: 10.4103/eus.eus_100_17
|View full text |Cite
|
Sign up to set email alerts
|

Patient perception and preference of EUS-guided drainage over percutaneous drainage when endoscopic transpapillary biliary drainage fails: An international multicenter survey

Abstract: Background and Objectives:EUS-guided biliary drainage (EUS-BD) is a feasible procedure when ERCP fails, as is percutaneous transhepatic BD (PTBD). However, little is known about patient perception and preference of EUS-BD and PTBD.Patients and Methods:An international multicenter survey was conducted in seven tertiary referral centers. In total, 327 patients, scheduled to undergo ERCP for suspected malignant biliary obstruction, were enrolled in the study. Patients received decision aids with visual representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…However, in addition to the high morbidity and reduced quality of life with PTBD, a recent international survey demonstrated that many patients (not surprisingly) would prefer internal BD over an external drain. 86 As a result, a growing number of studies have explored EUS-BD role in managing BBD. 10 11 21 83 87–92…”
Section: Benign Biliary Diseasementioning
confidence: 99%
“…However, in addition to the high morbidity and reduced quality of life with PTBD, a recent international survey demonstrated that many patients (not surprisingly) would prefer internal BD over an external drain. 86 As a result, a growing number of studies have explored EUS-BD role in managing BBD. 10 11 21 83 87–92…”
Section: Benign Biliary Diseasementioning
confidence: 99%
“…This is due to the risks of accidental dislocation of an external drainage tube and recurrent infections, which have a significant negative impact on quality of life. From a patient standpoint, the possibility of internal drainage is appealing due to convenience and likely improved quality of life, which is supported by a multicenter survey in which more than 80 % of patients preferred EUS-BD over PTBD 4 . Historical surgical biliary bypass is seldom used as the preferred treatment option because it is associated with higher morbidity and mortality 5 6 .…”
Section: Introductionmentioning
confidence: 99%
“…While often technically successful, PTBD has several notable disadvantages including risk of bleeding, bile leakage, pain at the insertion site and cosmetic dissatisfaction 2 3 . As a result, PTBD is associated with a decrease in patient quality of life and patients overwhelmingly prefer internal biliary drainage when possible 4 5 .…”
Section: Introductionmentioning
confidence: 99%